Effect of fluoride application during radiotherapy on enamel demineralization - Camila de Carvalho Almança Lopes; Carlos José Soares; Vitor Carvalho Lara; Victor Elias Arana-Chavez; Priscilla Barbosa Soares; Veridiana Resende Novais (University of São Paulo, 2018)
Abstract Radiation-related caries are one the most undesired reactions manifested during or after head and neck radiotherapy. Fluoride application is an important strategy to reduce demineralization and enhance remineralizaton. Objective: To evaluate the effect of the topical application of fluoride during irradiation on dental enamel demineralization. Material and Methods: Thirty molars were randomly divided into three groups: Non-irradiated (NI), Irradiated (I), Irradiated with fluoride (IF). Each group was subdivided according to the presence or absence of pH-cycling (n=5). In the irradiated groups, the teeth received 70 Gy. The enamel's chemical composition was measured using Fourier Transform Infrared Spectrometry (organic matrix/mineral ratio - M/M and relative carbonate content - RCC). Vickers microhardness (VHN) and elastic modulus (E) were evaluated at three depths (surface, middle and deep enamel). Scanning electron microscopy (SEM) was used to assess the enamel's morphology. Results: The FTIR analysis (M/M and RCC) showed significant differences for irradiation, pH-cycling and the interaction between factors (p<0.001). Without pH-cycling, IF had the lowest organic matrix/mineral ratio and relative carbonate content. With pH-cycling, the organic matrix/mineral ratio increased and the relative carbonate content decreased, except for IF. VHN was influenced only by pH-cycling (p<0.001), which generated higher VHN values. ANOVA detected significant differences in E for irradiation (p<0.001), pH-cycling (p<0.001) and for the interaction between irradiation and pH-cycling (p<0.001). Increased E was found for group I without pH-cycling. With pH-cycling, groups I and IF were similar, and showed higher values than NI. The SEM images showed no morphological changes without pH-cycling. With pH-cycling, fluoride helped to maintain the outer enamel's morphology. Conclusions: Fluoride reduced mineral loss and maintained the outer morphology of irradiated and cycled enamel. However, it was not as effective in preserving the mechanical properties of enamel. Radiotherapy altered the enamel's elastic modulus and its chemical composition.